Uber confesses to covering up breach. Issue 12 (December 2017) - Unknown
Abstract : Pseudo-taxi firm Uber has revealed that its systems were breached in 2016 and data relating to 57 million customers was stolen. The firm also confessed that it paid the hackers 100, 000, disguised as a bug bounty, for a promise that the data would be deleted.